Accelerated reactions of amines with carbon dioxide driven by superacid at the microdroplet interface - Huang, Kai-Hung; Wei, Zhenwei; Cooks, R. Graham (Chemical science (Cambridge), 2020)
Microdroplets display distinctive interfacial chemistry, manifested as accelerated reactions relative to those observed for the same reagents in bulk. Carbon dioxide undergoes C-N bond formation reactions with amines at the interface of droplets to form carbamic acids. Electrospray ionization mass spectrometry displays the reaction products in the form of the protonated and deprotonated carbamic acid. Electrosonic spray ionization (ESSI) utilizing carbon dioxide as nebulization gas, confines reaction to the gas-liquid interface where it proceeds much faster than in the bulk. Intriguingly, trace amounts of water accelerate the reaction, presumably by formation of superacid or superbase at the water interface. The suggested mechanism of protonation of CO 2 followed by nucleophilic attack by the amine is analogous to that previously advanced for imidazole formation from carboxylic acids and diamines. Microdroplets display distinctive interfacial chemistry, manifested as accelerated reactions relative to those observed for the same reagents in bulk.